Relationship between Interleukin 6 Serum Levels and Degree of Depression in Systemic Lupus Erythematosus Patients Internal Disease in Dr. Moh Hoesin Palembang - Shinta Suharno; Eddy Mart Salim; Ali Apriansyah; Taufik Indrajaya; Zen Ahmad; Erial Bahar (HM Publisher, 2021)
Introduction. Systemic Lupus Erythematosus (LES) is a chronic autoimmune inflammatory disease affecting many organ systems with varied clinical manifestations, disease course and prognosis. One of the clinical manifestations that can occur is depression as much as 25%. In LES patients, there is an increase in proinflammatory cytokines, one of which is IL-6, which is often associated with contributing to the pathophysiology of depression. The purpose of this study was to determine the relationship between serum IL-6 levels and the degree of depression in LES patients at RSUP DR. Mohammad Hoesin Palembang. Methods. Analytic observational study in the form of correlation test with cross sectional design which was conducted in the Internal Medicine room RSUP DR. Mohammad Hoesin Palembang from May 2019 to March 2020. The number of study subjects was 40 samples who were LES patients with depression who had been calculated using the BDI (Beck's Depression Inventory). All subjects were examined for serum IL-6 levels and evaluated for factors that influence it. Results. There were 40 study subjects aged 18-56 years. The median degree of depression was 16 with a range of values from 10 to 40. There were 17 people (42.5%) with mild depression degree, 14 people (35%) moderate depression, and 9 people (22.5%) major depression. In LES activities, there were 5 people (12.5%) with light LES activities, 20 people (50%) with moderate LES activities, and 15 people (37.5%) with heavy LES activities. The mean serum IL-6 level was 11.57 pg / mL with a value range of 1.1-50pg / mL. There was a significant correlation between the degree of depression and LES activity (p = 0.004; r = 0.444) and between serum IL-6 levels and the degree of depression (p = 0.025; r = 0.169). However, there was no significant correlation between serum IL-6 levels and LES activity (p = 0.057; r = 0.304). Conclusion. There is a relationship between serum IL-6 levels and the degree of depression in LES patients at Dr. Moh. Hoesin Palembang with a very weak correlation.